Vote Buying in Indonesia The Mechanics of Electoral Bribery - Muhtadi, Burhanuddin (Springer Nature, 2019)
This book is open access under a CC BY 4.0 license. This book investigates the impact of vote buying on the accountability of democratic institutions and policy representation in newly democratic countries, with a focus on Indonesia. In doing so, the book presents a wide-ranging study of the dynamics of vote buying in Indonesia's young democracy, exploring the nature, extent, determinants, targeting and effectiveness of this practice. It addresses these central issues in the context of comparative studies of vote buying, arguing that although party loyalists are disproportionately targeted in vote buying efforts, in total numbers -given the relatively small number of party loyalists in Indonesia- vote buying hits more uncommitted voters. It also demonstrates that the effectiveness of vote buying on vote choice is in the 10 percent range, which is sufficient for many candidates to secure a seat and thus explains why they still engage in vote buying despite high levels of leakage.